The effect of erythrocyte membranes from diabetic and hypercholesterolemic individuals on human carbonic anhydrase II activity. (1st January 2016) - Yildirmis, Sermet; Alver, Ahmet; Yandi, Yunus Emre; Demir, Selim; Senturk, Ayse; Bodur, Akin; Mentese, Ahmet
Abstract: Context : Erythrocyte membranes regulate many enzyme activities, including carbonic anhydrase II (CA II). Membrane fluidity is associated with alterations in protein function and protein-protein interactions. Objective : The purpose of this study was to show the human CA II (hCA II) activity regulation by human erythrocyte membranes from diabetic and hypercholesterolemic subjects. Materials and methods : Erythrocyte membranes were obtained from diabetic, hypercholesterolemic, and healthy subjects. hCA II activity was measured using the electrometric method. Results : hCA II activity was increased in vitro by membranes from both diabetic and hypercholesterolemic patients, with hypercholesterolemic membranes exhibiting a greater increase. Conclusion : Changes in membrane composition may affect the erythrocyte membranes' capacity to increase in vitro hCA II activity.